Elucidating the Mechanism of Weissella-dependent Lifespan Extension in Caenorhabditis elegans - Lee, Jiyun (Sci Rep, 2015)
The mechanism whereby lactic acid bacteria extend the lifespan of Caenorhabditis elegans has previously been elucidated. However, the role of Weissella species has yet not been studied. We show that Weissella koreensis and Weissella cibaria significantly (p < 0.05) extend the lifespan of C. elegans compared with Escherichia coli OP50 and induce the expression of several genes related to lifespan extension (daf-16, aak-2, jnk-1, sod-3 and hif-1). Oral administration of Weissella altered reactive oxygen species (ROS) production and lowered the accumulation of lipofuscin and increased locomotor activity (which translates to a delay in ageing). Moreover, Weissella-fed C. elegans had decreased body sizes, brood sizes, ATP levels and pharyngeal pumping rates compared with E. coli OP50-fed worms. Furthermore, mutations in sod-3, hif-1 or skn-1 did not alter lifespan extension compared with wild-type C. elegans. However, C. elegans failed to display lifespan extension in loss-of-function mutants of daf-16, aak-2 and jnk-1, which highlights the potential role of these genes in Weissella-induced longevity in C. elegans. Weissella species extend C. elegans lifespan by activating DAF-16 via the c-Jun N-terminal kinase (JNK) pathway, which is related to stress response, and the AMP-activated protein kinase (AMPK)-pathway that is activated by dietary restriction.